Workplace spirituality and knowledge sharing behaviour: an empirical study among non-academic staff of higher learning institutions - Rahman, Muhammad Sabbir; Mat Daud, Nuraihan; Osman-Gani, AAhad M.; Moudud, Hasan (2015)
This article aims to determine the relationship between workplace spirituality and knowledge sharing behaviour among non-academic staff of higher learning institutions in Malaysia. Since, there is an easy access to information and knowledgeable personnel at a higher learning institution, it is interesting to see if the non-academic staff seizes this opportunity to seek knowledge and share it with their colleague. Generally the staff are followers of the major religions in the world. In these faiths, the followers are encouraged to seek and share knowledge. In Malaysia, it is assumed that staff working at a university exercise their religious obligations and practices. Survey items were developed to measure their spirituality level and their knowledge sharing behaviour. A total of 200 questionnaires were completed by these non-academic staff. Applied confirmatory factor analysis and structural equation modelling (SEM) were used to assess the measurement model and to test the research hypotheses. The findings indicate that there was a significantly positive relationship between the staff’s spirituality in the workplace and their knowledge sharing behaviour. This study offers a fresh frame of reference for interpreting the relationship between workplace spirituality and knowledge sharing behaviour.